Problem Solving Ability Considered by Self Confidence in Digital Media Assisted Online Learning - Risma Astutiani; Isnarto Isnarto (Universitas Negeri Semarang, 2021)
The aims of this research are to know the Problem-Solving Ability (PSA) in Missouri Mathematics Project (MMP) assisted by digital media and Discovery Learning (DL) models to achieve learning mastery, to know the comparison of PSA of MMP assisted by digital media and DL, and to know how PSA students based on Self Confidence (SC) of low and high category. Subjects are 12 students who are unique in the results of the PSA test and self confidence questionnaire. Data collection using documentation, questionnaire, test, and interview. The result is 16 out of 26 students achieved individual mastery, so the percentage of classical completeness was 61,54%, which means that the experimental class hadn't yet reached 80% classical completeness; the PSA of MMP model assisted by digital media is better than DL model; students with high category sc achieve good criteria on each PSA indicators, whereas learners with low category SC achieve good criteria at the first PSA indicator. Tujuan penelitian mengetahui ketuntasan klasikal Kemampuan Pemecahan Masalah (KPM) pada pembelajaran daring model Missouri Mathematics Project (MMP) berbantuan media digital; mengetahui perbandingan KPM peserta didik model MMP berbantuan media dengan model Discovery Learning (DL); mengetahui KPM peserta didik model MMP berbantuan media digital ditinjau dari self confidence (sc). Penentuan sampel dan subjek menggunakan teknik purposive sampling. Subjek penelitian 12 peserta didik yang memiliki keunikan pada hasil tes KPM dan angket sc pada kelas eksperimen. Pengambilan data penelitian menggunakan dokumentasi, angket, tes, dan wawancara. Hasil penelitian 16 dari 26 peserta didik mencapai ketuntasan individual, sehingga persentase ketuntasan klasikal 61,54% yang artinya kelas eksperimen belum mencapai ketuntasan klasikal 80%, KPM peserta didik model MMP berbantuan media digital lebih baik daripada KPM peserta didik model DL, dan Peserta didik dengan sc tinggi mencapai kriteria baik pada setiap indikator KPM, sedangkan peserta didik dengan sc rendah mencapai kriteria baik pada indikator KPM pertama.